Ethical Issues in Neurotrauma: Challenges and Solutions - Khizar, Ahtesham; Ghafoor, Abdul; Elahi, Inaam (Indian Journal of Neurotrauma, 2023)
Neurotrauma is a medical field that deals with the treatment and prevention of serious injuries to the brain, spinal cord, or peripheral nerves. It presents complex ethical issues that require careful consideration and balance between individual autonomy, public health, patient preferences, and clinical outcomes. In this review, we examine several ethical dilemmas in neurotrauma, including the prevention of traumatic events, obtaining informed consent and respecting patient preferences in situations of impaired cognition and communication, determining the appropriate use of life-saving interventions, and communicating with patients and families about prognosis and outcomes. Our analysis highlights the need for a nuanced and evidence-based approach that takes into account the unique circumstances of each patient and balances the potential benefits and risks of various interventions.
Keywords: ethics; traumatic brain injuries; nervous system trauma; decompressive craniectomy; regenerative medicine